Subsidized debt, corporate governance, and ownership concentration of Brazilian firms - Sampaio, Thicia Stela Lima; Crisóstomo, Vicente Lima; Brandão, Isac de Freitas; Pinheiro, Bruno Goes (Review of Business Management, 2024)
Purpose – This paper evaluates the influence of corporate governance and ownership concentration on incentivized financing in Brazil. Theoretical framework – The effect of governance and ownership concentration on incentivized debt is analyzed from the perspective of agency conflicts (Agency Theory) and company behavior in relation to debt (Trade off and Pecking Order Theories). Design/methodology/approach – Corporate governance is approximated by an index and presence on the Novo Mercado. Models are estimated by FGLS and Logit for a panel with 1387 annual observations of 147 companies with more liquidity on B3 in the period 2010-2019. Findings – Ownership concentration has a positive quadratic relationship with Incentivized debt, which was not sensitive to corporate governance. There is a preference for incentivized debt by managers in companies with low ownership concentration and by controlling shareholders in companies with high concentration. The more lenient monitoring from incentivized debt’s creditor may be an explanatory factor. In addition, companies with high ownership concentration face difficulties for share issuance and consider it uninteresting. All that leads these firms to intensify debt raising. Research Practical & Social implications – It may be interesting for the government strengthening the analysis of corporate governance aspects in the assignment of incentivized credit. Originality/value – The recent evolution and the determinants of incentivized debt in Brazil are analyzed under the agency conflicts approach. This is an innovative approach that takes into account the specialization of debt composition and an important funding source. Keywords – Incentivized Debt; Corporate Governance; Ownership Concentration; Trade Off Theory; Agency Theory.